Trimester-specific reference intervals of serum homocysteine levels for pregnant women: a longitudinal study in China - Hai Liu; Qing Li; Ting Liu; Yuanting Tang; Fan Yu (Taylor & Francis Group, 2023)
Objective To investigate the physiological changes of serum homocysteine (Hcy) levels and to establish trimester-specific reference intervals of serum Hcy levels for Chinese pregnant women.Method According to the guideline of the Clinical and Laboratory Standards Institute (CLSI) C28-A3 document, 476 healthy women were recruited in West China Second University Hospital, Sichuan University from January 2021 to October 2021. Among them, 120 were non-pregnant, 118 were in the first trimester, 120 were in the second and 118 were in the third trimester of gestation. The enzymatic cycling method was performed to detect serum Hcy levels. Non-parametric percentiles (2.5th percentile and 97.5th percentile) were calculated to establish the reference intervals for non-pregnant women and pregnant women in different trimester of gestation.Results There was a significant statistical difference for serum Hcy levels between non-pregnant women and pregnant women (p < 0.05), and serum Hcy levels in the first, second, and third trimesters of gestation were statistically different (p < 0.05). The trimester-specific reference intervals of serum Hcy levels were 4.35 ∼ 10.16 μmol/L, 3.38 ∼ 8.60 μmol/L, and 3.75 ∼ 11.17 μmol/L for pregnant women in the first, second, and third trimester of gestation, respectively.Conclusions Compared to non-pregnant women, serum Hcy levels physiologically decreased after pregnancy, and the physiological changes in serum Hcy levels during pregnancy were also found. Establishing trimester-specific reference intervals of serum Hcy levels for pregnant women was valuable for clinical practice.